2008
DOI: 10.4067/s0717-95022008000300010
|View full text |Cite
|
Sign up to set email alerts
|

Inmunohistochemical Expression of PCNA, p53 and bcl-2 in Pleomorphic Adenomas

Abstract: GORDÓN-NÚÑEZ SUMMARY:The aim of the study was to determine the immunohistochemical expression of the PCNA, p53 and bcl-2 proteins in pleomorphic adenomas. Nineteen specimens of pleomorphic adenomas were selected for analysis by the streptavidin-biotin-peroxidase method with antibodies against p53, PCNA and bcl-2 proteins. It was observed weak labeling for p53 in 12 cases (63.1%) and for PCNA in 8 (42.1%). With respect to the bcl-2 labeling index, no expression of this protein was detected in 12 cases, correspo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…As nuclear size is a very important parameter, which changes in dysplasia and reflects the intensified DNA synthesis, and the abnormalities of nuclear features have been reported in various types of carcinoma, 43 , 44 morphological characteristics of PCNA-IR nuclei were investigated. Obtained results revealed that there was no significant differences in diameter and area of nuclei after administration of PAMAM-NH 2 at concentrations up to 3 mg/mL ( Figure 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…As nuclear size is a very important parameter, which changes in dysplasia and reflects the intensified DNA synthesis, and the abnormalities of nuclear features have been reported in various types of carcinoma, 43 , 44 morphological characteristics of PCNA-IR nuclei were investigated. Obtained results revealed that there was no significant differences in diameter and area of nuclei after administration of PAMAM-NH 2 at concentrations up to 3 mg/mL ( Figure 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…Cells with no P 53 expression can potentially replicate with damaged DNA, leading to malignant change (24). Many studies have correlated the expression of normal and mutant p53 with the differentiation, aggressiveness, and progression of salivary glands tumors, but the results are highly controversial (25–27). This study indicates that P 53 was negative for about 70% of PA cases.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, 93.3% of PA, 96.6% of AdCC, and 100% of MEC samples showed PCNA expression, which was in line with the study of Gordón-Núñez et al . [ 29 ] and contrary to the studies of Russo et al . [ 30 ], Perez et al .…”
Section: Discussionmentioning
confidence: 63%